Safety analysis of X-ray radiation exposure in installation - Iqna, Iqna Purwitasari; Nugroho, Anshor; Utami, Asih Puji (Universitas 'Aisyiyah Yogyakarta, 2025)
Radiology is important in early detection and risk assessment through real-time imaging. However, radiation safety in radiology installations remains a major concern in protecting patients, medical personnel, and the public from ionizing radiation exposure to avoid exceeding the Dose Limit Value (NBD). This study aims to analyse the results of X-ray radiation exposure and evaluate the radiation safety procedures implemented to reduce the risk of radiation exposure in the Radiology Installation of Panti Nugroho Sleman Hospital. The method used in this research is qualitative with an experimental approach conducted at Radiology Installation of Panti Nugroho Hospital Sleman in August 2024 - January 2025. Data collection was carried out at 10 measurement points where each point was measured three times then the measurement results were calculated using the formula and then compared with BAPETEN Regulation No. 5 of 2016. The results obtained are the value of radiation exposure measurements for 10 points of measurement area on conventional aircraft, namely 0 µSv / hour, 0 µSv / hour, 0.03 µSv / hour, 0 µSv / hour, 0.33 µSv / hour, 0.03 µSv / hour, 0 µSv / hour, 0.13 µSv / hour, 0.03 µSv / hour, and 0 µSv / hour. As well as radiation exposure measurement values for 10 points of measurement area in the panoramic plane, namely 0 µSv/hour, 0 µSv/hour, 0 µSv/hour, 0 µSv/hour, 0.03 µSv/hour, 0 µSv/hour, 0 µSv/hour, 0 µSv/hour, 0 µSv/hour, 0 µSv/hour. In addition, standard operating procedures such as room management, equipment maintenance, provision of aprons, implementation of radiation exposure testing, use of TLD (Thermoluminescence Dosimeter), and health checks have been implemented in a structured manner in order to prevent and protect the safety of all parties and the environment. It is expected that this research can be useful for health aspects for radiation workers such as being able to identify ways to reduce radiation exposure in order to avoid stochastic effects, gene mutations, and so on by developing more effective safety protocols to reduce X-ray radiation exposure for radiology workers and the public.